Executive Committee Minutes 2020-04-23 - Academic Senate:::::::::
Agenda Approved. Minutes of 4/9/2020 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice President of Administration and Finance Report. Vice Chair Report. Vice President for Student Affairs Report. From FSAC: Policy revision: RTP policy - G. Levels and Sequence of RTP Review #2 and #3 – Approved for Senate Agenda. From EPC: Internship Policy – Approved for Senate Agenda. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Senate Agenda approved.